Study of direct nanoimprinting processes by molecular dynamics simulations - Pei, Qing Xiang (2012)
The direct nanoimprinting process between a diamond mold and a copper substrate is studied using molecular dynamics simulations with embedded atom method potential. The deformation behavior, dislocation movement and imprint force are investigated. For the three imprint surfaces of (0 0 1), (1 1 0) and (1 1 1), it is found that the (0 0 1) surface results in the lowest imprint force, while the (1 1 1) surface results in the highest one. When imprinting on the (0 0 1) surface, the dislocations glide in an angle of about 45° to the imprint direction. In contrast, the dislocations move in parallel or normal to the imprint direction when imprinting on the (1 1 0) surface. For imprinting on the (1 1 1) surface, the dislocations glide in a small angle or normal to the imprint direction. The mold taper angle has little effect on the dislocation moving directions, though it has strong influence on the substrate deformation and imprint forces.